Benefits and limits of peer support for mothers with intellectual disability affected by domestic violence and child protection. Issue 3 (15th March 2020) - Collings, Susan; Strnadová, Iva; Loblinzk, Julie; Danker, Joanne
Abstract: It is established that parents with intellectual disability raise their children in conditions of severe socio-economic disadvantage, increasing the risk of child removal. Peer support can help vulnerable and isolated families engage with social services and assist parents to navigate the child protection system. Despite this, little is known about the experience of peer support for parents with intellectual disability. An inclusive research study involving 26 parents with intellectual disability was undertaken to understand their views of peer support. Inductive content analysis identified three themes. One theme, coping with adversity, explored peer support for a sub-group of parents ( n  = 10) who had experienced domestic and family violence or had a child removed from their care, in some cases both. Their experiences of peer support to cope with these challenges are discussed, as well as implications for research and practice.